The Effect of Monaurally Fitted Hearing Aid Use on the Evolution of Presbycusis. (September 2021) - Dunya, Gabriel; Najem, Fadi; Mailhac, Aurelie; Abou Rizk, Samer; Bassim, Marc
Objective: The effect of hearing aid use on the evolution of presbycusis has not been well described in the literature, with only a handful of publications addressing this topic. This paper aims to evaluate the long-term use of amplification and its effect on pure-tone thresholds and word recognition scores. Method: Monaurally fitted patients were followed with serial audiograms. Data was collected from hearing aid centers. Seventy-seven patients with presbycusis met the inclusion criteria and participated in the present study. The progression of hearing loss in both pure tone thresholds and word recognition scores were compared between the hearing aid ears (HA), and the non-hearing aid ears (NHA). Pure tone thresholds were analyzed by comparing the pure tone average at the initial and last audiograms. Word Recognition Scores (WRS) were analyzed using the model of Thornton and Raffin (1978), and by comparing the change in the absolute values of WRS from the initial to the last audiogram between the HA ear and the NHA ear. Results: No significant difference in pure-tone thresholds between the HA ear and NHA ear was found at the last audiogram ( P  = .696), even after dividing the patients into groups based on the duration of amplification. Both methods of analysis of patients' WRS showed a statistically significant worsening in NHA ( P  < .05). Conclusion: The present study supports the previously defined auditory deprivation effect on non-fitted ears, which showed worsening of word recognition over time and no effect on pure tone average. It provides an additional argument for the counseling of patients with presbycusis considering amplification, and highlights the importance of bilateral amplification in preserving the residual hearing of hearing impaired patients.